LEGAL IMPLICATIONS OF REGULATING ARTICLES 38 AND 39 OF LAW NUMBER 1 OF 2023 (CRIMINAL CODE) ON CRIMINAL LIABILITY FOR PERSONS WITH DISABILITIES - Canthika Mira Istiyanthi; Faizin Sulistio; Abdul Madjid (CV. RADJA PUBLIKA, 2025)
This research analyzes the juridical implications of Articles 38 and 39 of Law Number 1 of 2023 (Criminal Code) on the construction of criminal liability for persons with disabilities in Indonesia's criminal justice system. Through a juridical-normative approach, the research identifies a paradigmatic transformation from a paternalistic model toward a rights-based approach, albeit with implementation challenges encompassing conceptual ambiguities, procedural limitations, and structural barriers. The findings demonstrate the urgency of reorienting criminal liability construction through developing a